Do Biotic and Abiotic Factors Influence the Prevalence of a Common Parasite of the Invasive Alien Ladybird Harmonia axyridis? - Haelewaters, Danny; Hiller, Thomas; Ceryngier, Piotr; Eschen, René; Gorczak, Michał; Houston, Makenna L.; Kisło, Kamil; Knapp, Michal; Landeka, Nediljko; Pfliegler, Walter P.; Zach, Peter; Aime, M. Catherine; et al. (Frontiers in Ecology and Evolution, 2022)
Hesperomyces virescens (Ascomycota, Laboulbeniales), a fungal ectoparasite, is thus far reported on Ha. axyridis from five continents: North and South America, Europe, Africa, and Asia. While it is known that He. virescens can cause mortality of Ha. axyridis under laboratory conditions, the role of biotic and abiotic factors in influencing the distribution of He. virescens in the field is unknown. We collected and screened 3,568 adult Ha. axyridis from 23 locations in seven countries in Central Europe between October and November 2018 to test the effect of selected host characters, as well as climate and landscape variables, on the infection probability with He. virescens. Mean parasite prevalence of He. virescens on Ha. axyridis was 17.9%, ranging among samples from 0% to 46.4%. Host sex, climate, and landscape composition did not have any significant effect on the infection probability of He. virescens on Ha. axyridis. Two color forms, f. conspicua and f. spectabilis, had a significant lower prevalence of infection compared to the common Ha. axyridis f. novemdecimsignata.